Comparing Beneish and Dechow Model in Predicting Financial Shenanigans: Evidence from Energy Sector in Emerging Market - Febrianti, Vina; Septian, Defel; Sayuti, Alfian; Khairunnisa, Khairunnisa; Lestari, Ayu Ambang (Master of Accounting Universitas Trunojoyo Madura, 2026)
Based on a 2024 ACFE survey, financial statement fraud is the type of fraud that causes the highest average loss compared to other types. Several approaches exist for predicting financial statement fraud, including the Beneish M-Score (hereafter M-Score) and Dechow F-Score (hereafter F-Score). The purpose of this study is to evaluate which model best predicts financial statement fraud in Indonesia’s energy industry. The research sample was determined using a purposive sampling method. The sample consists of 140 financial statements from energy sector companies listed on the Indonesia Stock Exchange from 2020 to 2024 that were indicated to be free from violations related to their financial reporting. The results reveal that the F-Score model is more effective in detecting financial statement fraud in energy companies, with a 100% accuracy rate and a 0% error rate, while the M-Score model obtained a 73% accuracy rate and a 27% error rate. This research is expected to provide implications for stakeholders in selecting the right model to predict financial statement fraud, especially in energy sector.